Keragaman dan Kelimpahan Serangga Tanaman Cabai Merah (Capsicum annum L.) Berefugia Kembang Kotokan (Tagetes erecta L.) - M. Agung Saputra M; Suswati Suswati; Asmah Indrawati (Universitas Medan Area, 2022)
This study aims to determine the index of diversity and abundance of insects in red chili with refugia flower kotokan (Tagetes erecta L.) The method used in this study was descriptive analysis using ordinal sampling using a non-factorial randomized block design. This research was carried out in the experimental garden of the Faculty of Agriculture, Medan Area University, from April to June 2021. The insect traps used were yellow sticky traps, pitfall traps, and sweep nets. The results showed an abundance of 2,972 insects consisting of 11 insect orders, 34 insect families and 39 species. Insects from the family Tettigoniidae had the highest value of 10.53%. While the value of predatory insects is 5.15%. from the family Formicidae. The value of the diversity index in the red chili plant area with Tagetes erecta L was (H') 3.3045 (height). The value of the evenness index of insect species (E') in the area of red chili with refugia was 0.902 (quite abundant).